Assessing livestock herding practices of agro-pastoralists in western Bhutan: Livestock vulnerability to predation and implications for livestock management policy - Tshering, Kencho; Thinley, Phuntsho (Pastoralism : research, policy and practice, 2017)
As in many developing countries, agro-pastoralism is the major form of livelihood for rural communities in the Himalayan Kingdom of Bhutan. Although livestock rearing is part and parcel of rural Bhutanese agricultural system, Bhutan also has a high percentage of natural forest cover that supports a diversity of endangered wild predators. The loss of cattle to these predators is an on-going source of conflict between predators, farmers, and wildlife managers. Despite awareness of predation losses, there has been no empirical assessment of livestock herding practices in Bhutan in terms of livestock vulnerability to predation. We conducted a questionnaire and a field survey in three districts of western Bhutan to assess current livestock herding practices with regard to predation vulnerability. We interviewed farmers using a semi-structured questionnaire to determine their livestock herding practices and losses. We also traversed human trails in the nearby forests and took note of livestock encountered to gain further insights into herding dynamics. Generally, livestock were more vulnerable to predation when released into the forests without accompanying herders. Seasonally, livestock were more vulnerable during summer and early autumn, which coincided with the peak farming period during which animals are typically released into forests with minimal care. Our study underscores the importance of livestock herding with accompanying herders to minimize predation losses and highlights the challenges posed by farm labour shortage in rural areas. We recommend developing a comprehensive livestock management policy that includes elaborate provisions on reducing livestock losses through livestock herd management, stock improvement, fodder development, pasture development, and sustainable livestock insurance schemes.